PROBLEMATIKA HUKUM FUNGSI REKRUITMEN ORGANISASI SAYAP PARTAI POLITIK - Abd. Rais Asmar (Paulus Law Journal, 2021)
The success of the performance of the political recruitment function by Political Parties departs from its cadre mechanism. This is supported by the regeneration of a good and responsible wing organization of political parties. This study aims to determine legal problems related to the function of the wing organization of political parties. The type of research in this writing is normative legal research, with a statutory approach and a literature approach. This research examines the laws and regulations on political parties and related legal norms. The data used are secondary data consisting of primary and secondary legal materials. Primary legal materials are in the form of Law Number 2 of 2008 concerning Political Parties, while secondary legal materials are in the form of books, journals and articles related to the topic of the problem. The results showed that there were still several problems, such as the lack of rules governing the Organization of the Political Party Wing and the activities of cadres related to their location and background.